Investigations on the charge compensation on Ca and U substitution in CePO4 by using XPS, XRD and Raman spectroscopy. Issue 3 (April 2015) - Asuvathraman, R.; Gnanasekar, K.I.; Clinsha, P.C.; Ravindran, T.R.; Govindan Kutty, K.V.
Abstract: This article discusses the charge compensation mechanism in Ca and U - substituted monazite (CePO4 ). The monazite compositions Ce0.6 Ca0.2 U0.2 PO4, Ce0.8 Ca0.2 PO4 and CePO4 were prepared by solution chemistry route. XRD and μ-Raman studies confirm that the compounds are single phase materials. XPS studies on Ce0.8 Ca0.2 PO4 shows the presence of Ce 4+ in addition to Ce 3+ whereas in Ce0.6 Ca0.2 U0.2 PO4 cerium is in +3 state with uranium in +4 valence state. Partial substitution of Ca in CePO4 (i.e. Ce0.8 Ca0.2 PO4 ), leads to the generation of Ce 4+ which subsequently reverts to Ce 3+ in Ce0.6 Ca0.2 U0.2 PO4 upon U substitution. The C e 3 + ⇌ C e 4 + intrinsic charge compensation existing in monazite, essential for the incorporation of higher valence cations, is demonstrated. This mechanism assists the incorporation of M 2+/4+ in the monazite lattice without requiring coupled substitution.